2011
DOI: 10.1007/s11368-011-0390-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessing phytoremediation potentials of selected tropical plants for acrylamide

Abstract: Purpose Environmentally hazardous and health risk substances in animals and humans in the environment have increased as a result of continuing anthropogenic activities. Examples of these activities are food processing, laboratory, food production, industrial, and other relative activities that use various forms of acrylamide. All acrylamide in the environment are manmade. It is the building block for the polymer, polyacrylamide, which is considered to be a nontoxic additive. However, if the polymerization proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Phytoremediation requires somewhat limited resources and is very useful in treating a wide variety of environmental contaminants. It is in this context that Uera et al [63] conducted a study aimed to assess the potential of selected tropical plants as phytoremediators of EtBr. This study used tomato (Solanum lycopersicum), mustard (Brassica alba), vetiver grass (Viteveria zizanioides), cogon grass (Imperata cylindrical), carabao grass (Paspalum conjugatum) and talahib (Saccharum spontaneum) to remove EtBr from laboratory wastes.…”
Section: Phytoremediation Potential Of Selected Plants For Mutagenic mentioning
confidence: 99%
See 2 more Smart Citations
“…Phytoremediation requires somewhat limited resources and is very useful in treating a wide variety of environmental contaminants. It is in this context that Uera et al [63] conducted a study aimed to assess the potential of selected tropical plants as phytoremediators of EtBr. This study used tomato (Solanum lycopersicum), mustard (Brassica alba), vetiver grass (Viteveria zizanioides), cogon grass (Imperata cylindrical), carabao grass (Paspalum conjugatum) and talahib (Saccharum spontaneum) to remove EtBr from laboratory wastes.…”
Section: Phytoremediation Potential Of Selected Plants For Mutagenic mentioning
confidence: 99%
“…However, the absorption capabilities of the other test plant may also be considered in terms of period of maturity and productivity. Uera et al [63] recommended that a more detailed and complete investigation of the phytoremediation properties of the different plants tested should be conducted in actual field experiments. Plants should be exposed until they reach maturity to establish their maximum response to the toxicity and mutagenecity of EtBr and their absorbing capabilities.…”
Section: Phytoremediation Potential Of Selected Plants For Mutagenic mentioning
confidence: 99%
See 1 more Smart Citation
“…Cu 2+ , Cd 2+ , Zn 2+ ), as soluble complexes with organic or inorganic ligands (e.g. ZnCl + , CdCl 3 -, metal citrates) and associated with colloidal materials. Severe heavy metal contamination in soil may cause a variety of problems, including the reduction of yield and metal toxicity of plants, animals and humans.…”
Section: Introductionmentioning
confidence: 99%
“…Indian mustard plants over-expressing APS have increased tolerance and accumulation of selenium (Pickering et al, 2000). Paz-Alberto et al (2011) had assessed phytoremediation potentials of selected tropical plants for acrylamide. They found that mustard and pechay were the most effective to absorb the highest acrylamide concentrations in their root, shoot, and the whole plants.…”
Section: Introductionmentioning
confidence: 99%